Vascular Smooth Muscle Cell Stiffness and Adhesion to Collagen I Modified by Vasoactive Agonists - Hong, Zhongkui (PLoS One, 2015)
In vascular smooth muscle cells (VSMCs) integrin-mediated adhesion to extracellular matrix (ECM) proteins play important roles in sustaining vascular tone and resistance. The main goal of this study was to determine whether VSMCs adhesion to type I collagen (COL-I) was altered in parallel with the changes in the VSMCs contractile state induced by vasoconstrictors and vasodilators. VSMCs were isolated from rat cremaster skeletal muscle arterioles and maintained in primary culture without passage. Cell adhesion and cell E-modulus were assessed using atomic force microscopy (AFM) by repetitive nano-indentation of the AFM probe on the cell surface at 0.1 Hz sampling frequency and 3200 nm Z-piezo travelling distance (approach and retraction). AFM probes were tipped with a 5 μm diameter microbead functionalized with COL-I (1mg\ml). Results showed that the vasoconstrictor angiotensin II (ANG-II; 10(−6)) significantly increased (p<0.05) VSMC E-modulus and adhesion probability to COL-I by approximately 35% and 33%, respectively. In contrast, the vasodilator adenosine (ADO; 10(−4)) significantly decreased (p<0.05) VSMC E-modulus and adhesion probability by approximately −33% and −17%, respectively. Similarly, the NO donor (PANOate, 10(−6) M), a potent vasodilator, also significantly decreased (p<0.05) the VSMC E-modulus and COL-I adhesion probability by −38% and −35%, respectively. These observations support the hypothesis that integrin-mediated VSMC adhesion to the ECM protein COL-I is dynamically regulated in parallel with VSMC contractile activation. These data suggest that the signal transduction pathways modulating VSMC contractile activation and relaxation, in addition to ECM adhesion, interact during regulation of contractile state.